The importance of hypertensive control in chronic renal patients: a literature review (Research, Society and Development, 2022)
Systemic arterial hypertension (SAH) is characterized by increased blood pressure, influenced by several factors (heredity, socioeconomic aspects and lifestyle) and affecting several target organs, such as the heart, vessels, brain and kidneys. Given this, among the main diseases caused by SAH, chronic kidney disease (CKD) stands out. This pathology is defined as the progressive and irreversible loss of nephrons (functional units of the kidney), with a consequent decrease in the glomerular filtration rate and/or increased excretion of albumin in the urine. In this regard, the main objective of this scientific article is to discuss the importance of blood pressure control in the treatment of chronic kidney disease, addressing relevant topics on the subject and bringing a review of the current bibliography. Thus, 58 articles were selected, which went through exclusion criteria (identification, screening, eligibility and inclusion), totaling, for the final analysis, 22 articles. The search was carried out in the following databases: Virtual Health Library (BVS), Scientif Electronic Library Online (SciELO), National Library of Medicine (PubMed), and Google School. Furthermore, the descriptors used were: “chronic kidney disease”, “hypertension”, “diagnosis”, “treatment”, “pressure control”; and to cross words, the Boolean operator “and” was used. The searches were limited to articles published between 2018 and 2022, in Portuguese, English or Spanish. After the analysis, it was evident that hypertensive control, both through pharmacological interventions and through behavioral and lifestyle changes, brought beneficial results for chronic kidney disease patients, reducing the progression of CKD.